COMPETENCE CRITERIA OF TEACHERS AT BLENDED LEARNING OF ENGINEERING STUDENTS - Kateryna A. Ivanova; Oleksandr M. Alekseev (Information technologies and learning tools, 2017)
The work is devoted to the definition of competence criteria of teachers in the mixed (hybrid) education of engineering students. The study was conducted based on generalization of known competence criteria of teachers of traditional education and analysis of publications of domestic and foreign authors devoted to the problems of mixed education. The competence criteria of the teachers in mixed training of engineering students were proposed, an expert evaluation of the importance of each criterion was conducted using the non-parametric Friedman criterion. 27 criteria which are most significant for assessing the competence of teachers in the mixed education of engineering students were identified. Taking into account the specificity of the teacher's work in mixed education, the singled out competence criteria were divided into three subgroups.